The Addition Effect of Cheese to Tempeh Against Flavor, Function, and Product Attractiveness - Novianti, Riska T; Dewi, Lusiawati; Situmorang, Risya Pramana (AGRITEKNO: Jurnal Teknologi Pertanian, 2022)
Tempeh is a type of soybean-based food made by a fermentation process. Processing soybeans into tempeh can involve adding natural additives to increase nutritional value and to make it more fulfilled. Cheese is a food derived from animal milk with high protein content. Adding cheese to soybean tempeh fermentation can increase tempeh protein so that the protein in tempeh consists of vegetable and animal protein. The study's objective was to measure protein content, moisture content, and organoleptic tests (taste, smell, color, and mycelial appearance) on tempeh when given cheese powder. The method used is firstly drying cheese into powder, then making tempeh with cheese powder added to various concentrations (0%, 0.5%, 1%, 1.5%, and 2%). The Lowry method tested the protein content, while the water content was tested using gravimetry. An organoleptic test was carried out based on several parameters: odor, taste, color, and mycelium density. Results from this study, the results of the increase in protein levels from each given concentration. The water content did not provide a significantly different effect from any given concentration of cheese. And based on the organoleptic test, the addition of cheese to tempeh did not affect the mycelium's color, taste, smell, and density. Adding cheese to soybean tempeh can be an alternative in increasing protein content; besides, adding cheese does not significantly affect the product's taste, smell, color, and Mycelium distribution density.